Interactions between adenosine, angiotensin II and nitric oxide on the afferent arteriole influence sensitivity of the tubuloglomerular feedback - Persson, A. Erik G.; Lai, En Y.; Gao, Xiang; Carlström, Mattias; Patzak, Andreas (Frontiers in Physiology, 2013)
Adenosine, via activation of A1 receptors on the afferent arteriole (AA), mediates the tubuloglomerular feedback (TGF) mechanism. Angiotensin II and nitric oxide (NO) can modulate the sensitivity of the TGF mechanism. However, the interaction among these substances in regulating the TGF resetting phenomenon has been debated. Studies in isolated perfused AA have shown a biphasic response to accumulating doses of adenosine alone. In the nanomolar range adenosine has a weak contractile effect (7%), whereas vasodilatation is observed at high concentrations. However, a synergistic interaction between the contractile response by adenosine and that of angiotensin II has been demonstrated. Adenosine in low concentrations strongly enhances the response to angiotensin II. At the same time, angiotensin II in physiological concentrations increases significantly the contractile response to adenosine. Moreover, addition of a NO donor (spermine NONOate) to increase NO bioavailability abolished the contractile response from combined application of angiotensin II and adenosine. These mutual modulating effects of adenosine and angiotensin II, and the effect of NO on the response of AA can contribute to the resetting of the TGF sensitivity.